2018
DOI: 10.1186/s12882-018-1144-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of standard and low dose hydrochlorothiazide in the recurrence prevention of calcium nephrolithiasis (NOSTONE trial): protocol for a randomized double-blind placebo-controlled trial

Abstract: BackgroundNephrolithiasis is a global healthcare problem with a current lifetime risk of 18.8% in men and 9.4% in women. Given the high cost of medical treatments and surgical interventions as well as the morbidity related to symptomatic stone disease, medical prophylaxis for stone recurrence is an attractive approach. Thiazide diuretics have been the cornerstone of pharmacologic metaphylaxis for more than 40 years. However, evidence for benefits and harms of thiazides in the prevention of calcium containing k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
16
0
2
Order By: Relevance
“…Stone event rates in these pooled empagliflozin trials were similar to what has been observed in the general population in individuals with diabetes in three large prospective US cohorts (Nurses’ Health Study I, the Nurses’ Health Study II and the Health Professionals Follow-up Study) 16. RCTs testing dietary or pharmacologic measures for recurrence prevention typically included patients with stone event rates between 20 and 200 events/100 person-years 33 34. Hence, if recurrence prevention of kidney stones by SGLT2 inhibitors will indeed prove effective and safe, individuals with high rates of stone formation would especially benefit from treatment.…”
Section: Introductionsupporting
confidence: 60%
“…Stone event rates in these pooled empagliflozin trials were similar to what has been observed in the general population in individuals with diabetes in three large prospective US cohorts (Nurses’ Health Study I, the Nurses’ Health Study II and the Health Professionals Follow-up Study) 16. RCTs testing dietary or pharmacologic measures for recurrence prevention typically included patients with stone event rates between 20 and 200 events/100 person-years 33 34. Hence, if recurrence prevention of kidney stones by SGLT2 inhibitors will indeed prove effective and safe, individuals with high rates of stone formation would especially benefit from treatment.…”
Section: Introductionsupporting
confidence: 60%
“…The sequence of events that triggers stone formation comprises of nucleation, growth, aggregation, and retention of crystals in the kidneys. Reportedly, controlling crystal-cell retentions is one of the best ways to treat urolithiasis [9]. Of note, NOX4 is a transmembrane transporter that transports electrons out of the serosa to produce superoxide and other reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, lower doses of thiazides are often employed aiming to reduce metabolic adverse effects, but their efficacy as such is not well established 3,21,33 . In order to clarify these unsolved questions, a 3-year prospective double-blind ongoing trial was initiated in 2017 with the purpose of assessing the efficacy of standard and low dose HCTZ in the recurrence prevention of calcium stone formation 34 . Notwithstanding the evidence of lower stone recurrence on thiazides compared to placebo, it is worth mentioning that most of the aforementioned studies had been conducted along the 1980s and 1990s.…”
Section: Metabolic and Clinical Aspects Of Thiazide And Thiazide-likementioning
confidence: 99%